Unforeseen diversity of quails (Galliformes: Phasianidae: Coturnix) in oceanic islands provided by the fossil record of Macaronesia - Rando, J. Carlos; Alcover, Josep Antoni; Pieper, Harald; Olson, S. L.; Hernández, C. Nayra; López-Jurado, Luis F. (Oxford University Press, 2020)
The original bird fauna of most oceanic islands has been affected by recent extinction processes associated with human arrival and its subsequent impacts. In the volcanic Macaronesian archipelagos (Azores, Madeira, Selvagens, Canary Islands and Cape Verde), in the North Atlantic, the Late Quaternary fossil record indicates that there was formerly a higher avian diversity, including a high number of now extinct endemic species. This assemblage of extinct birds includes endemic insular quails (Galliformes: Phasianidae). In this study, we describe three newly discovered extinct species of quails, two of which inhabited the archipelago of Madeira (Coturnix lignorum sp. nov. from Madeira Island and Coturnix alabrevis sp. nov. from Porto Santo Island) and one from Cape Verde (Coturnix centensis sp. nov.). The fossil record also indicates the presence of additional species of extinct endemic quails on other Macaronesian islands. These birds plus the extinct Canary Island quail (Coturnix gomerae) indicate a high former endemic diversity of this genus in Macaronesia, a feature unique among oceanic archipelagos. Anatomical traits show that the new taxa were flightless ground dwellers, making them vulnerable to human interference, with their extinction being linked to human arrival and subsequent habitat alterations and the introduction of invasive species. This research was supported by project CGL2016-79795-R, ‘Cambios holocénicos en la biodiversidad animal de las islas de la Macaronesia y de Baleares. II', funded by the Agencia Estatal de Investigación (Ministerio de Economía, Industria y Competitividad)/Fondo Europeo de Desarrollo Económico y Regional.